Serum Levels of CXCL-13, RBP-4, and IL-6, and Correlation Analysis of Patients with Graves’ Disease - Yanqin Hu; Yue Sun; Yuxuan Huang; Qiuxia Liu; Fan Ren (Emergency Medicine International)
Objective. To investigate the serum levels of CXC chemokine 13 (CXCL-13), retinol binding protein-4 (RBP-4), and interleukin 6 (IL-6) in patients with Graves’ disease (GD). The correlation between CXCL-13, RBP-4, and IL-6 levels and the basal metabolic rate (BMR) was analyzed. Methods. 118 GD patients diagnosed in our hospital were selected as the observation group from March 2017 to December 2018. According to the measured BMR value, 118 GD patients were divided into the mild group (n = 39), the moderate group (n = 47), and the severe group (n = 32), three subgroups. 60 healthy subjects were selected as the control group. The serum levels of CXCL-13, RBP-4, IL-6, TSH, FT3, and FT4 in every group were measured. Pearson correlation analysis was used to observe the correlation of serum CXCL-13, RBP-4, and IL-6 levels with TSH, FT3, FT4, and BMR. Results. The levels of serum CXCL-13, RBP-4, and IL-6 in the observation group were higher than those of the control group, and the differences were statistically significant (P<0.05). The levels of serum CXCL-13, RBP-4, and IL-6 in the moderate and severe groups were higher than those in the mild group, and the differences were statistically significant (P<0.05). The levels of serum CXCL-13, RBP-4, and IL-6 in the severe group were higher than those in the moderate group, and the differences were statistically significant (P<0.05). Pearson correlation analysis showed that the serum levels of CXCL-13, RBP-4, and IL-6 in GD patients were negatively correlated with TSH levels and positively correlated with FT3 and FT4 levels. Serum CXCL-13, RBP-4, and IL-6 levels in GD patients were positively correlated with BMR (r = 0.915, r = 0.942, r = 0.926, P<0.001). Conclusion. Serum CXCL-13, RBP-4, and IL-6 levels are elevated in patients with GD, and with the aggravation of the disease, the serum CXCL-13, RBP-4, and IL-6 levels also increase, showing a positive correlation, which can be used as indicators to reflect the degree of GD.